Awareness Mentality and Strategic Behavior in Science - Ball, Rafael (Frontiers in Research Metrics and Analytics, 2021)
Acknowledgement of scientific achievements was and is essentially achieved through the citation of a publication. Increasingly, however, it is no longer just the publication itself that plays an important role, but also the degree of attention that a scientist achieves with this very publication. Thus, the importance of strategic behavior in science is progressing and an awareness mentality is spreading. In this paper, the causes and backgrounds of this development are discussed, as well as the forms of strategic behavior in science and the resulting consequences and impacts.